FUNGSI PRAGMATIK UNGKAPAN ARAB DALAM INTERAKSI MAHASISWA UIN WALISONGO SEMARANG: ANALISIS SOSIOPRAGMATIK - Zainurrakhmah; Namira Choirani Fajri (Universitas Muhammadiyah Makassar, 2026)
This study examines the pragmatic functions of Arabic expressions in the oral conversations of students at UIN Walisongo Semarang within the context of religious-academic interaction. Prior research has largely emphasized code-switching classifications and social factors, while the dimensions of illocution, discourse management, and relational distribution remain underanalyzed in an integrated manner, particularly in naturalistic student interaction within Indonesian Islamic higher education (PTKIN). This study aims to identify the forms and contexts of Arabic expression use, analyze their functions as speech act realizations, discourse markers, and sociopragmatic markers, and explain their distribution across peer and hierarchical relationships. A qualitative sociopragmatic approach is employed, integrating Searle's speech act theory, Leech's politeness principles, Hymes' ethnography of communication, and Schiffrin's discourse marker framework. Data were collected through two months of natural conversation recordings involving 20 participants from multiple faculties, yielding 24 functionally classified types of Arabic expressions as units of analysis. The findings indicate that Arabic expressions function as multidimensional pragmatic resources realizing expressive, directive, assertive, and commissive speech acts, while simultaneously managing discourse structure and indexing deference in hierarchical relationships. The study concludes that Arabic expressions are undergoing indexical stabilization within the student speech community: rather than functioning merely as religious identity markers, they constitute a multifunctional pragmatic infrastructure that organizes discourse, manages social relations, and constructs normatively grounded commitments within a shared religious-academic environment. These findings carry implications for sociopragmatic theory and language education in PTKIN institutions.